1990
DOI: 10.1002/j.2161-0045.1990.tb00833.x
|View full text |Cite
|
Sign up to set email alerts
|

Annual Review: Practice and Research in Career Counseling and Development, 1989

Abstract: In writing this review, we asked ourselves what novel cut of the 1989 career literature we might make. Several earlier reviews were cleverly organized using the structure inherent in the research and theoretical literature published during the review period (Fitzgerald & Rounds, 1989;Savickas, 1989a). Other reviews selected articles for inclusion based on methodological rigor, author preference, or preponderance in number. We believed that it was possible to organize a selective review based upon counselor pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 123 publications
0
17
0
Order By: Relevance
“…The number of articles and journals represented in the reviews has grown over time. Each one of those 25 reviews provided a brief summary of the content of articles by topic, as well as a commentary on the nature of the literature published that year (Arbona, 2000;Bikos, Dykhouse, Boutin, Gowen, & Rodney, 2013;Chope, 2008;Cook, 1991;Creager, 2011;Dagley & Salter, 2004;Erford & Crockett, 2012;Flores et al, 2003;Guindon & Richmond, 2005;Harrington & Harrigan, 2006;Hartung, 2010;Jepsen, 1992;Luzzo & MacGregor, 2001;Niles, 1997;Patton & McIlveen, 2009;Salomone, 1993;Savickas, 1989;Spokane & Hawks, 1990;Stoltz-Loike, 1996;Subich, 1994;Swanson & Parcover, 1998;Tien, 2007;Walsh & Srsic, 1995;Whiston & Brecheisen, 2002;Young & Chen, 1999). In reviewing past CDQ annual reviews, we identified some noteworthy trends.…”
mentioning
confidence: 99%
“…The number of articles and journals represented in the reviews has grown over time. Each one of those 25 reviews provided a brief summary of the content of articles by topic, as well as a commentary on the nature of the literature published that year (Arbona, 2000;Bikos, Dykhouse, Boutin, Gowen, & Rodney, 2013;Chope, 2008;Cook, 1991;Creager, 2011;Dagley & Salter, 2004;Erford & Crockett, 2012;Flores et al, 2003;Guindon & Richmond, 2005;Harrington & Harrigan, 2006;Hartung, 2010;Jepsen, 1992;Luzzo & MacGregor, 2001;Niles, 1997;Patton & McIlveen, 2009;Salomone, 1993;Savickas, 1989;Spokane & Hawks, 1990;Stoltz-Loike, 1996;Subich, 1994;Swanson & Parcover, 1998;Tien, 2007;Walsh & Srsic, 1995;Whiston & Brecheisen, 2002;Young & Chen, 1999). In reviewing past CDQ annual reviews, we identified some noteworthy trends.…”
mentioning
confidence: 99%
“…All search techniques except 1 revealed interaction effects, favoring or limiting graduates with specific characteristics such as appropriate specialization and higher ability. Direct contact with employers and early initiation of search contributed directly to initial baccalaureate-level employment.As Spokane and Hawks (1990) described it in 1990, research on the transition to work for college graduates remains, with the broader literature on job search, "perhaps the most understudied area in contemporary career development" (p. 11 1). The broad dimensions of job search have been identified, but only a few areas of investigation are well enough developed to support major generahzations and principles regarding job seeking.…”
mentioning
confidence: 99%
“…Even though early aspirations may be similar among social groups, the resources and opportunities needed to implement these aspirations differ sharply across groups. What we are beginning to understand is that different, and in many cases more powerful, barriers present themselves to women and minorities than to other social groups (Carter & Cook, 1992;Gottfredson, 1986;Spokane & Hawks, 1990). The probability of implementing a n aspiration is, then, less for some social groups than for others.…”
Section: Career Aspirations and Events That Shape Themmentioning
confidence: 99%
“…An Accurate Framework for Organizing and Filtering Information Perhaps the most frequent presenting complaint that clients make in career counseling is that they simply do not know how to proceed in making a career decision. This prdblem has been called lack of structure (0s-ipow, 1987) and is repeatedly found to be troubling (Spokane & Hawks, 1990).…”
Section: Everything You Need To Know About Career Developmentmentioning
confidence: 99%